Assessing the research use and needs of organizations promoting healthy living for adults with disabilities. Issue 1 (20th August 2013) - Sweet, Shane N; Latimer-Cheung, Amy E; Bourne, Chris; Ginis, Kathleen A Martin
Abstract: The uptake of research in community-based organizations (CBOs) is low and still unknown in CBOs that promote active and healthy living in adults with a disability. Using the knowledge to action framework, the objectives of this study were to determine if a gap exists regarding the use of research in CBOs, to learn about the preferred method to receive/read research evidence and to identify the barriers and facilitators of research use. Sixty-two employees of CBOs answered an online questionnaire. A research use gap was found as only 53 % of employees indicated they often or always use research. Conferences, emails and short research summaries were the favoured method of receiving/reading research information. Education, time and financial resources were important barriers to research use, while attitudes, intentions and self-efficacy were facilitators. More efforts are needed to develop tools to help CBOs use research.